Montecuccoli’s Fame, or: A Diplomat’s Military Reputation at the Swedish Court in 1654 - Christof Muigg (Theatrum Historiae)
This article is about the weight of military fame in the inaugural audience of Imperial general and diplomat Raimondo Montecuccoli (1609–1680) at the Swedish court in 1654. The assumption is, that Montecuccoli’s military fame was a resource for him as a diplomat. Military fame was a resource because it was symbolic capital that mediated Montecuccoli’s reputation in the language of symbolic communication. How military fame worked in the language of symbolic communication is discussed by looking at Raimondo Montecuccoli’s Swedish journal. Montecuccoli’s own account is contrasted by the Swedish journal of the English ambassador Bulstrode Whitelocke (1605–1675), who was at the Swedish court at the same time.